Phosphorus-based porous carbon composite material, preparation method thereof, negative electrode and lithium ion battery

By using the heat treatment method of porous carbon materials prepared by biomass and red phosphorus, a phosphorus-based porous carbon composite material is formed, which solves the problem of RP shedding and aggregation of phosphorus-carbon composite materials in lithium-ion batteries, and achieves high discharge specific capacity and fast charging stability.

CN119695110AActive Publication Date: 2025-03-25SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411853673.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing phosphorus-carbon composite materials have problems such as RP shedding and aggregation, hindering Li+ diffusion, resulting in sudden capacity attenuation and slow electrochemical reaction kinetics in the negative electrode materials of lithium-ion batteries.

Method used

Biomass is used as a carbon source to prepare porous carbon materials with specific porous structures, and red phosphorus is effectively anchored on the porous carbon material through heat treatment to form a phosphorus-based porous carbon composite material.

Benefits of technology

It improves the discharge specific capacity and long-term fast charging stability of lithium-ion batteries, avoids the shedding and aggregation of RP, enhances Li+ diffusion and electron transmission, and optimizes the cyclic stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695110A_ABST
    Figure CN119695110A_ABST
Patent Text Reader

Abstract

The invention provides a phosphorus-based porous carbon composite material, a preparation method thereof, a negative electrode and a lithium ion battery, and the preparation method comprises the following steps: S1, carrying out etching treatment on a biomass carbon source by adopting an acidic etching agent to obtain a precursor; s2, performing first heat treatment on the precursor to obtain a porous carbon material; the temperature of the first heat treatment is 600-1000 DEG C; s3, carrying out second heat treatment on the porous carbon material and red phosphorus to obtain a phosphorus-based porous carbon composite material; the temperature of the second heat treatment is 460-800 DEG C. According to the preparation method of the phosphorus-based porous carbon composite material provided by the invention, the porous carbon material with a specific pore structure is prepared by taking biomass as a carbon source, and red phosphorus is effectively anchored on the obtained porous carbon material; the lithium ion battery subsequently prepared from the phosphorus-based porous carbon composite material disclosed by the invention has relatively high specific discharge capacity and excellent long-term rapid charging stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a phosphorus-based porous carbon composite material, a preparation method thereof, a negative electrode and a lithium ion battery. Background Art

[0002] Phosphorus (P) has attracted extensive attention as anode material for lithium-ion batteries (LIBs) due to its high theoretical specific capacity (2595 mAh / g) and safe working potential (0.75 V). Among the allotropes of phosphorus, red phosphorus (RP), white phosphorus (WP), black phosphorus (BR), and purple phosphorus (VR), RP has low commercial cost, abundant resources, easy processing, and stable chemical properties at room temperature, making it more suitable as anode material for lithium batteries. In order to solve the problems of large volume expansion (about 300% for lithium batteries) and poor conductivity (10 -4 In order to solve the problem of reducing the conductivity of RP (S / cm), combining RP with a highly conductive carbon matrix (carbon black, carbon nanotubes, graphene, porous carbon) is considered to be an effective method. Among these matrices, porous carbon materials have attracted increasing attention due to their advantages of sufficient space to load RP and high conductivity.

[0003] However, the configuration of most porous carbon materials is relatively simple, which easily leads to the shedding and aggregation of RP in the internal space, hindering the Li + Diffusion results in insufficient utilization of active materials, and is also prone to cause sudden capacity decay and sluggish electrochemical reaction kinetics, hindering the large-scale application of phosphorus-carbon composite materials in lithium-ion battery negative electrode materials. Summary of the invention

[0004] In order to solve the above-mentioned defects existing in the prior art, the present invention provides a phosphorus-based porous carbon composite material, a preparation method thereof, a negative electrode, and a lithium-ion battery. The preparation method of the phosphorus-based porous carbon composite material provided by the present invention uses biomass as a carbon source to prepare a porous carbon material with a specific pore structure, and effectively anchors red phosphorus on the obtained porous carbon material. Under the synergistic effect of the two, the lithium-ion battery prepared by using the phosphorus-based porous carbon composite material of the present invention has a high discharge specific capacity and excellent long-term fast charging stability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a phosphorus-based porous carbon composite material, which comprises the following steps:

[0007] S1: etching the biomass carbon source with an acidic etchant to obtain a precursor;

[0008] S2: subjecting the precursor to a first heat treatment to obtain a porous carbon material;

[0009] The temperature of the first heat treatment is 600-1000°C;

[0010] S3: subjecting the porous carbon material and red phosphorus to a second heat treatment to obtain a phosphorus-based porous carbon composite material;

[0011] The temperature of the second heat treatment is 460-800°C.

[0012] In some preferred embodiments, in step S1, the biomass carbon source includes one or more of longan core, papaya seed core, apple core and cherry core, for example: longan core or papaya seed core.

[0013] In some preferred embodiments, in step S1, a pre-treatment operation is also included before the etching process.

[0014] In some more preferred embodiments, in step S1, the pretreatment operation is to grind the dried biomass carbon source into powder and then pass it through a 100-mesh sieve to obtain a sieve out.

[0015] In the above scheme, the pulverization is preferably carried out using a traditional Chinese medicine pulverizer.

[0016] In the above scheme, the drying temperature is preferably 100-120° C., for example, 110° C.; the drying time is preferably 8-16 hours, for example, 12 hours.

[0017] In some preferred embodiments, in step S1, the etching treatment is performed by immersing the biomass carbon source in an acidic etchant.

[0018] In the above scheme, the acidic etchant preferably includes one or more of hydrochloric acid and sulfuric acid, for example: 0.5M HCl solution or 0.4M H2SO4.

[0019] In the above scheme, the etching process is preferably performed under stirring; the stirring time is preferably 15 to 25 hours, for example: 20 hours.

[0020] In some preferred embodiments, in step S2, the first heat treatment is performed under an inert atmosphere, such as nitrogen and / or argon.

[0021] In some preferred embodiments, in step S2, the heating rate of the first heat treatment is 3-5°C / min.

[0022] In some preferred embodiments, in step S2, the temperature of the first heat treatment is 600-800°C.

[0023] In some preferred embodiments, in step S2, the first heat treatment lasts for 2 to 4 hours. The first heat treatment lasts for 2 to 4 hours. The first heat treatment lasts for 2 to 4 hours.

[0024] In some preferred embodiments, in step S2, the first heat treatment is followed by grinding, washing and drying operations.

[0025] In the above scheme, the grinding operation is preferably to grind the material after the first heat treatment into a powder with a particle size of 10 to 20 μm; the grinding operation is preferably carried out using one or more of a jaw crusher, a double-roll crusher and a jet mill, and more preferably using a jaw crusher, a double-roll crusher and a jet mill in sequence.

[0026] In the above scheme, the washing operation is preferably performed using clean water.

[0027] In the above scheme, the drying temperature is preferably 100-120° C., for example, 110° C.; the drying time is preferably 2-6 hours, for example, 4 hours.

[0028] In some preferred embodiments, in step S3, the red phosphorus is micron-sized red phosphorus, preferably red phosphorus with a particle size range of 5 to 50 μm.

[0029] In some preferred embodiments, in step S3, the mass ratio of the porous carbon material to the red phosphorus is 1:(1-1.1), for example: 1:1.

[0030] In some preferred embodiments, in step S3, the second heat treatment is performed in a vacuum reactor.

[0031] In some preferred embodiments, in step S3, the second heat treatment is performed under an inert atmosphere, such as nitrogen and / or argon.

[0032] In some preferred embodiments, in step S3, the heating rate of the second heat treatment is 3-5°C / min, for example, 4°C / min.

[0033] In some preferred embodiments, in step S3, the temperature of the second heat treatment is 500-650°C, for example, 600°C.

[0034] In some preferred embodiments, in step S3, the second heat treatment time is 2 to 4 hours. The second heat treatment time is the time for keeping the temperature at the second heat treatment temperature.

[0035] In some preferred embodiments, in step S3, the second heat treatment further includes cooling, washing and drying operations.

[0036] In the above scheme, the cooling operation is preferably to cool the material after the second heat treatment to 240-260°C and then keep it warm for 18-30 hours, more preferably to cool it to 240°C and then keep it warm for 24 hours, and finally cool it to room temperature.

[0037] In the above scheme, the washing operation is preferably performed using CS2.

[0038] In the above scheme, the drying temperature is preferably 100-120° C., for example, 110° C.; the drying time is preferably 2-4 hours.

[0039] The present invention provides a phosphorus-based porous carbon composite material, which is prepared by the method for preparing the phosphorus-based porous carbon composite material as described above.

[0040] The present invention provides a phosphorus-based porous carbon composite material, which comprises a porous carbon material and phosphorus deposited inside the pores of the porous carbon material;

[0041] The average particle size of the porous carbon material is 10 to 20 μm; the specific surface area of ​​the porous carbon material is 1300 to 1500 m 2 / g;

[0042] The microporosity of the porous carbon material is 70% to 80%; the micropore volume of the porous carbon material is 0.4 to 0.6 cm 3 / g; the average pore diameter of the porous carbon material is 0.35 to 0.5 nm;

[0043] The mesoporosity of the porous carbon material is 20% to 30%; the mesopore volume of the porous carbon material is 0.1 to 0.2 cm 3 / g; the average pore size of the mesopores of the porous carbon material is 3 to 4.5 nm;

[0044] The mass percentage of the porous carbon material in the phosphorus-based porous carbon composite material is 50% to 60%; the mass percentage of the phosphorus in the phosphorus-based porous carbon composite material is 40% to 50%.

[0045] In some preferred embodiments, the average particle size of the porous carbon material is 18 μm.

[0046] In some preferred embodiments, the specific surface area of ​​the porous carbon material is 1358 m 2 / g or 1477m 2 / g.

[0047] In some preferred embodiments, the microporosity of the porous carbon material is 76.30% or 77.23%.

[0048] In some preferred embodiments, the micropore volume of the porous carbon material is 0.512 cm 3 / g or 0.519cm 3 / g.

[0049] In some preferred embodiments, the average pore size of the micropores of the porous carbon material is 0.4 nm or 0.44 nm.

[0050] In some preferred embodiments, the mesoporosity of the porous carbon material is 22.77% or 23.70%.

[0051] In some preferred embodiments, the mesopore volume of the porous carbon material is 0.153 cm 3 / g or 0.159cm 3 / g.

[0052] In some preferred embodiments, the average mesopore diameter of the porous carbon material is 3.45 nm or 4.2 nm.

[0053] In some preferred embodiments, the porous carbon material accounts for 54% or 57% by mass of the phosphorus-based porous carbon composite material.

[0054] In some preferred embodiments, the mass percentage of phosphorus in the phosphorus-based porous carbon composite material is 43% or 46%.

[0055] In the present invention, pores with a diameter less than 2 nm are called micropores; pores with a diameter between 2 and 50 nm are called mesopores (or medium pores); and pores with a diameter greater than 50 nm are called macropores.

[0056] The present invention also provides a negative electrode, which is the phosphorus-based porous carbon composite material as described above.

[0057] The present invention also provides a lithium ion battery, which comprises the negative electrode as described above.

[0058] The present invention uses degradable biological waste to prepare oxygen self-doped hierarchical porous carbon materials, and uses them as carriers of RP. Through the steam-condensation method, RP is converted into WP vapor. Under the action of capillary force and pressure difference, WP vapor diffuses and fills into the pores of the porous carbon material, mainly into micropores. After cooling, it is converted into nano-scale red phosphorus (NRP, a P4 small molecule with a regular tetrahedron at 600°C and a side length of 0.221nm) and anchored in the micropores through the space confinement effect to obtain a phosphorus-based porous carbon composite material. Among them, the micropores can effectively buffer the volume expansion of RP during the cycle; the mesopores can provide sufficient space for the electrolyte, promoting Li+ diffusion; at the same time, the high conductivity of carbon itself is beneficial to the rapid transmission of electrons, thereby improving the fast charging performance of lithium-ion batteries, giving them a higher discharge specific capacity and excellent long-term fast charging stability, and thus having great commercial feasibility.

[0059] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0060] The reagents and raw materials used in the present invention are commercially available.

[0061] The positive and progressive effects of the present invention are:

[0062] (1) The phosphorus-based porous carbon composite material prepared by the present invention has a richer pore structure, which can reduce the volume change of the active material RP while avoiding its shedding and aggregation during the subsequent battery cycle, effectively increasing the utilization rate and cycle stability of RP, greatly improving the fast charging stability of lithium-ion batteries, and optimizing the application of phosphorus-carbon composite materials in lithium-ion batteries.

[0063] (2) The preparation method of the phosphorus-based porous carbon composite material provided by the present invention uses biomass as a carbon source to prepare a porous carbon material with a specific pore structure, and effectively anchors red phosphorus on the obtained porous carbon material. Under the synergistic effect of the two, the lithium-ion battery subsequently prepared from the phosphorus-based porous carbon composite material of the present invention has a high discharge specific capacity and excellent long-term fast charging stability; and the method is low-cost and simple in process, which not only realizes the recycling of waste resources, but also has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is the SEM image of the phosphorus-based porous carbon composite material prepared in Example 1.

[0065] Figure 2 This is the XRD pattern of the phosphorus-based porous carbon composite material prepared in Example 1.

[0066] Figure 3 The charge and discharge curves of the first, second and 200th cycles of a lithium-ion battery prepared using the phosphorus-based porous carbon composite material prepared in Example 1 as the negative electrode material. DETAILED DESCRIPTION

[0067] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0068] In the embodiments and comparative examples of the present invention, longan seeds or papaya seed seeds can be obtained by peeling and pulping in a conventional manner; commercial micron-grade red phosphorus is purchased from Aladdin Reagent (Shanghai) Co., Ltd., with a particle size range of 5 to 50 μm.

[0069] Example 1

[0070] S1: Take 1000g of longan kernels dried at 110°C for 12h, crush them with a traditional Chinese medicine grinder, pass them through a 100-mesh sieve to obtain a sieve, and then perform an etching treatment, that is, soak the sieve in 5L of 0.5M HCl solution and stir for 20h to obtain a precursor;

[0071] S2: subjecting the precursor to a first heat treatment, the specific conditions are: nitrogen atmosphere, heating rate of 5°C / min, and heat preservation at 800°C for 2h; then, the material after the first heat treatment is ground into a powder with a particle size of 10 to 20 μm using a jaw crusher, a roll crusher and a jet mill, washed with clean water and dried at 110°C for 4h to obtain a porous carbon material;

[0072] S3: 200g of commercial micron-grade red phosphorus and 200g of the above-mentioned porous carbon material are uniformly mixed and placed in a vacuum autoclave for a second heat treatment. The specific conditions are: nitrogen atmosphere, heating rate 4°C / min, keeping warm at 500°C for 2h, then dropping to 240°C, keeping warm for 24h, and finally dropping to room temperature. Residual white phosphorus in the material is washed away with CS2, and dried at 110°C for 2h to obtain a phosphorus-based porous carbon composite material.

[0073] Example 2

[0074] S1: Take 1000g of papaya seed core dried at 110°C for 12h, crush it with a traditional Chinese medicine grinder, pass it through a 100-mesh sieve to obtain a sieve, and then perform an etching treatment, that is, soak the sieve in 5L of 0.5M HCl solution and stir for 20h to obtain a precursor;

[0075] S2: subjecting the precursor to a first heat treatment, the specific conditions are: argon atmosphere, heating rate of 3°C / min, and heat preservation at 600°C for 2h; then, the material after the first heat treatment is ground into a powder with a particle size of 10 to 20 μm using a jaw crusher, a roll crusher and a jet mill in sequence, washed with clean water and dried at 110°C for 4h to obtain a porous carbon material;

[0076] S3: 200g of commercial micron-grade red phosphorus and 200g of the above-mentioned porous carbon material are uniformly mixed and placed in a vacuum autoclave for a second heat treatment. The specific conditions are: argon atmosphere, heating rate 4°C / min, keeping warm at 600°C for 2h, then reducing to 240°C, keeping warm for 24h, and finally reducing to room temperature. Residual white phosphorus in the material is washed away with CS2, and dried at 110°C for 2h to obtain a phosphorus-based porous carbon composite material.

[0077] Comparative Example 1

[0078] 200g of commercial micron-grade red phosphorus and 200g of commercial porous carbon material (model CMK-3) were evenly mixed and placed in a vacuum autoclave for heat treatment. The specific conditions were: argon atmosphere, heating rate 4°C / min, keeping warm at 600°C for 2h, then dropping to 240°C, keeping warm for 24h, and finally dropping to room temperature. The residual white phosphorus in the material was washed away with CS2, and dried at 110°C for 2h to obtain a phosphorus-based porous carbon composite material.

[0079] Comparative Example 2

[0080] Commercial micron-sized red phosphorus is directly used as the negative electrode material.

[0081] Effect Example 1

[0082] Characterization of properties of phosphorus-based porous carbon composites

[0083] (1) Test method

[0084] The average particle size, specific surface area, microporosity, micropore volume, micropore average pore size, mesoporosity, mesopore volume and mesopore average pore size of the porous carbon materials of the above embodiments and comparative examples were characterized by using Autosorb iQ-3 fully automatic specific surface area and pore size analyzer.

[0085] The present invention uses a JSM-7500F scanning electron microscope to observe the microscopic morphology of the phosphorus-based porous carbon composite material of the above embodiment and comparative example. The present invention uses a Bruker D8 X-ray diffraction analyzer to analyze the crystal structure and phase composition of the phosphorus-based porous carbon composite material of the above embodiment and comparative example, and the radiation source uses Cu Kα. The scanning range is 10-80°, and the scanning speed is 10° / min.

[0086] (2) Test results

[0087] The test results are shown in Table 1 and Table 2.

[0088] Table 1

[0089]

[0090] Table 2

[0091]

[0092] It can be seen from Table 1 that the porous carbon material in the phosphorus-based porous carbon composite material prepared in the present application has a higher microporosity and a lower mesoporosity, and there are no macropores therein, while the conventional porous carbon material used in Comparative Example 1 has a mesoporosity of up to 91.10%, with almost no micropores. Figure 1This is a SEM image of the phosphorus-based porous carbon composite material prepared in Example 1; Figure 2 The XRD pattern of the phosphorus-based porous carbon composite material prepared in Example 1. Figure 2 It can be seen that the spectrum only shows a broad peak at 2θ≈23°, which can be attributed to the characteristic peak of amorphous carbon, while no peak of RP is observed, which indicates that RP has been successfully loaded into the pores of the phosphorus-based porous carbon composite material in the form of nanoparticles, mainly in the micropores, so the characteristic peak of RP is not shown.

[0093] Effect Example 2

[0094] Electrochemical performance test of lithium-ion batteries prepared from phosphorus-based porous carbon composites

[0095] (1) Test method

[0096] The product obtained in the embodiment or comparative example was mixed as the negative electrode material (80 wt%) with conductive carbon black (10 wt%) and polyvinylidene fluoride (10 wt%) as a binder, dissolved in NMP to prepare a uniform slurry, and the slurry was coated on a copper foil and dried at 60°C in vacuum for 10 h to obtain a negative electrode. The mass loading of the electrode was about 1.5 mg / cm 2 Lithium metal sheets were used as counter electrodes, 1 M LiPF6 dissolved in a mixture of EC and DEC (1:1 = v:v) was used as the electrolyte, and 2500 type PP film was used as the separator. Button cells (2025 type) were assembled in a glove box (Ar atmosphere).

[0097] The constant current charge and discharge test was carried out using a LAND tester at room temperature, with a voltage range of 0.01 to 2.5 V and a current density of 1 A / g.

[0098] (2) Test results

[0099] The test results are shown in Table 3.

[0100] Table 3

[0101]

[0102] The electrical properties of lithium-ion batteries obtained from the products obtained in Examples 1 and 2 were compared with those of Comparative Example 1, and it was found that the discharge specific capacity and capacity retention rate of the battery obtained from the phosphorus-based porous carbon composite material of the present invention were significantly higher than those of Comparative Example 1. Comparative Example 2 uses pure red phosphorus as the negative electrode material of the lithium-ion battery. The theoretical specific capacity of red phosphorus is as high as 2595mAh / g, but due to the lack of support from the carbon skeleton, it will produce huge volume expansion during the cycle, and will be crushed and fall off after the cycle, causing a rapid decrease in capacity, and the capacity retention rate is extremely low. The capacity shown in subsequent cycles should be the carbon capacity contribution of the conductive agent. Therefore, the phosphorus-based porous carbon composite material prepared by the present invention has good application prospects and high market value in improving the capacity and cycle stability of batteries.

Claims

1. A method for preparing a phosphorus-based porous carbon composite material, characterized in that: It includes the following steps: S1: etching the biomass carbon source with an acidic etchant to obtain a precursor; S2: subjecting the precursor to a first heat treatment to obtain a porous carbon material; The temperature of the first heat treatment is 600-1000°C; S3: mixing the porous carbon material and red phosphorus, and performing a second heat treatment to obtain a phosphorus-based porous carbon composite material; The temperature of the second heat treatment is 460-800°C.

2. The method for preparing the phosphorus-based porous carbon composite material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S1, the biomass carbon source includes one or more of longan core, papaya seed core, apple core and cherry core, for example: longan core or papaya seed core; (2) In step S1, a pre-processing operation is also included before the etching process; Preferably, the pretreatment operation is to grind the dried biomass carbon source into powder and then pass it through a 100-mesh sieve to obtain a sieve out; Wherein, the pulverization is preferably carried out by using a traditional Chinese medicine pulverizer; The drying temperature is preferably 100-120°C, for example 110°C; the drying time is preferably 8-16h, for example 12h; (3) In step S1, the etching treatment operation is to immerse the biomass carbon source in an acidic etchant; Wherein, the acidic etchant preferably includes one or more of hydrochloric acid and sulfuric acid, for example: 0.5M HCl solution or 0.4M H2SO4; The etching process is preferably carried out under stirring; the stirring time is preferably 15 to 25 hours, for example, 20 hours.

3. The method for preparing the phosphorus-based porous carbon composite material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S2, the first heat treatment is performed under an inert atmosphere, for example, nitrogen and / or argon; (2) In step S2, the heating rate of the first heat treatment is 3 to 5°C / min; (3) In step S2, the temperature of the first heat treatment is 600-800° C.; (4) In step S2, the first heat treatment time is 2 to 4 hours; (5) In step S2, the first heat treatment is followed by grinding, washing and drying operations; The grinding operation is preferably to grind the material after the first heat treatment into a powder with a particle size of 10 to 20 μm; the grinding operation is preferably performed by using one or more of a jaw crusher, a double-roll crusher and a jet mill, and more preferably by using a jaw crusher, a double-roll crusher and a jet mill in sequence; Wherein, the washing operation is preferably carried out using clean water; The drying temperature is preferably 100-120° C., for example, 110° C.; the drying time is preferably 2-6 hours, for example, 4 hours.

4. The method for preparing the phosphorus-based porous carbon composite material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) In step S3, the red phosphorus is micron-sized red phosphorus, preferably red phosphorus with a particle size range of 5 to 50 μm; (2) In step S3, the mass ratio of the porous carbon material to the red phosphorus is 1:(1-1.1), for example: 1:1; (3) In step S3, the second heat treatment is performed in a vacuum reactor; (4) In step S3, the second heat treatment is performed under an inert atmosphere, for example, nitrogen and / or argon; (5) In step S3, the heating rate of the second heat treatment is 3 to 5°C / min, for example, 4°C / min; (6) In step S3, the temperature of the second heat treatment is 500-650° C., for example, 600° C.; (7) In step S3, the second heat treatment time is 2 to 4 hours.

5. The method for preparing the phosphorus-based porous carbon composite material according to claim 4, characterized in that: In step S3, the second heat treatment is followed by cooling, washing and drying operations; The cooling operation is preferably to cool the material after the second heat treatment to 240-260°C and then keep it warm for 18-30 hours, more preferably to cool it to 240°C and then keep it warm for 24 hours, and finally cool it to room temperature; Wherein, the washing operation is preferably performed using CS2; The drying temperature is preferably 100-120° C., for example, 110° C.; the drying time is preferably 2-4 hours.

6. A phosphorus-based porous carbon composite material, characterized in that: The phosphorus-based porous carbon composite material is prepared by the preparation method of any one of claims 1 to 5.

7. A phosphorus-based porous carbon composite material, characterized in that: The phosphorus-based porous carbon composite material comprises a porous carbon material and phosphorus deposited inside the pores of the porous carbon material; The average particle size of the porous carbon material is 10 to 20 μm; the specific surface area of ​​the porous carbon material is 1300 to 1500 m 2 / g; The microporosity of the porous carbon material is 70% to 80%; the micropore volume of the porous carbon material is 0.4 to 0.6 cm 3 / g; the average pore diameter of the porous carbon material is 0.35 to 0.5 nm; The mesoporosity of the porous carbon material is 20% to 30%; the mesopore volume of the porous carbon material is 0.1 to 0.2 cm 3 / g; the average pore size of the mesopores of the porous carbon material is 3 to 4.5 nm; The mass percentage of the porous carbon material in the phosphorus-based porous carbon composite material is 50% to 60%; the mass percentage of the phosphorus in the phosphorus-based porous carbon composite material is 40% to 50%.

8. The phosphorus-based porous carbon composite material according to claim 7, characterized in that: The phosphorus-based porous carbon composite material meets one or more of the following conditions: (1) The average particle size of the porous carbon material is 18 μm; (2) The specific surface area of ​​the porous carbon material is 1358 m 2 / g or 1477m 2 / g; (3) The microporosity of the porous carbon material is 76.30% or 77.23%; (4) The micropore volume of the porous carbon material is 0.512 cm 3 / g or 0.519cm 3 / g; (5) The average pore size of the porous carbon material is 0.4 nm or 0.44 nm; (6) The mesoporosity of the porous carbon material is 22.77% or 23.70%; (7) The mesopore volume of the porous carbon material is 0.153 cm 3 / g or 0.159cm 3 / g; (8) The average pore size of the mesopores of the porous carbon material is 3.45 nm or 4.2 nm; (9) The mass percentage of the porous carbon material to the phosphorus-based porous carbon composite material is 54% or 57%; (10) The mass percentage of phosphorus in the phosphorus-based porous carbon composite material is 43% or 46%.

9. A negative electrode, characterized in that It comprises the phosphorus-based porous carbon composite material as claimed in any one of claims 6 to 8.

10. A lithium ion battery, characterized in that: It comprises the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Phosphorus-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery

    CN109216682A

  • Loofah sponge biomass carbon-loaded red phosphorus lithium ion battery negative electrode material and preparation method thereof

    CN111211308A

  • Method for preparing biomass carbon lithium ion battery anode material

    CN111653774A

  • Preparation method of porous hard carbon / red phosphorus composite material

    CN113307247A

  • Self-supporting cotton biomass carbon loaded red phosphorus sodium ion battery negative electrode material and preparation method thereof

    CN116759582A

Cited By

  • Super-capacitor carbon with high specific surface area and preparation method and application thereof

    CN121317731A

  • High specific surface area supercapacitor carbon, and preparation method and application thereof

    CN121317731B